Diverse Stills: Picturing the Landscape - Gray, Michael; Nathan, Tony; Tolonen, Juha (2019)
Research Background This body of work is a continuation of the series, ‘New Australian Plants and Animals’. It is informed by a synthesis of physiology, phenomenology and photographic technology whilst drawing on my personal experience as a non-indigenous Australian of multiple generations to provide contextual background for the creative work. Primarily, the intersection of research into physiology, photography and phenomenology is confined to the facticity of the human eye: how the physiology of the eye may unknowingly affect the experience of visual phenomena, and in turn, how you could possibly approach that ‘unknown’ aesthetic through creating works of art based on single element lenses. The images draw parallels between preconscious visual phenomena and the subjective experience of non-indigenous Australians of multiple generations. Research Contribution The practical outcomes can be seen to align aspects of phenomenology (Merleau-Ponty 1945/2013) and the optical unconscious (Benjamin, Jennings et al. 1931/2005). In phenomenological terms, the aesthetic produced privileges the biology of the human eye over the processing power of the visual cortex; a preconscious ocular aesthetic over conscious perception. When viewing images that approach a fundamental, yet unknown, visual experience the viewer partially has access to preconscious visual phenomenon. The results highlight how photography has always strived to produce a uniform, sharp plane of focus which in turn falsely maintains that human beings biologically experience the world in a similar manner. The work also promotes discussion on aspects of Maurice Merleau-Ponty’s (1945) ‘indeterminate vision’ and Walter Benjamin’s (1936) ‘optical unconscious’ whilst bringing the two together. The work also realises how an arts practice can incorporate the agency of materials (Carter, 2004) to approach traditionally intellectual enquiry in novel ways.